Epigraphs on seals in Southern Thailand: Concrete evidence of the India’s earliest contact with Suvarṇabhūmi - Wongsathit, U-tain; Mangmeesukhsiri, Sombat; Khatshima, Kangvol (Journal of Language and Culture, 2023)
This research article explores the significance of eleven seals and beads inscribed with Maurya Brahmi script discovered in the upper regions of southern Thailand. These artifacts, ranging from the 3rd century BCE to the 1st century CE, provide tangible evidence of early contact between India and Southeast Asia or Suvarṇabhūmi at the time. The study examines the origins and provenance of these epigraphs, highlighting their role in tracing the spread of Buddhism through trade routes. Furthermore, it investigates the influence of different castes, particularly the Vaishya and goldsmith castes, in promoting Buddhism and the intriguing presence of Brahmin-related inscriptions. By shedding light on the local artisans’ errors and the abundance of uninscribed seals, this article offers insights into the active trade network and cultural exchanges that shaped the region during the earliest period.